Nilai-Nilai Karakter Religius dalam Kegiatan Pencak Silat - Afif Putra Nazwan; Alfurqan Alfurqan (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to find out about the values ​​of religious character in the pencak silat activities of ISMD Putra Setia Nagari Sikabu. In this research, the researcher uses field research with a qualitative approach, a qualitative approach is a research method used to examine the condition of natural objects, where the researcher is the key instrument. In this study, the sources or informants were 2 teachers or trainers and 4 students from the ISMD Putra Setia college. Collecting data in this study using observation, interviews, and documentation. From the results of the study it was found that the values ​​of religious character in pencak silat activities among members of the Putra Setia Nagari Sikabu ISMD college, among others: 1) the existence of a disciplined attitude, 2) an honest attitude, 3) a polite attitude, 4) an attitude patient, 5) the attitude of responsibility, and 6) the attitude of hard work.